The 2021 ECtHR Decision in Georgia v Russia (II) and the Application of Human Rights Law to Extraterritorial Hostilities. Issue 2 (25th July 2022) - Longobardo, Marco; Wallace, Stuart
Abstract : This article discusses the findings of the European Court of Human Rights in the 2021 case of Georgia v Russia (II) in relation to the applicability of the European Convention on Human Rights to the conduct of hostilities. The article describes the arguments advanced by the Court to support the idea that the Convention does not apply to extraterritorial hostilities in an international armed conflict. In the light of past decisions, international humanitarian law, international human rights law, and the law of the treaties, it is argued that the Court's conclusion is unconvincing and the arguments seem to be based on extralegal considerations, rather than on a sound interpretation of the notion of state jurisdiction under the Convention.